The frequency of combination of pathological tooth attrition and malocclusion - K. I. Solodkaya; A. P. Chegodaeva (Сеченовский вестник, 2015)
Aim of the research was to distinguish a frequency of cases of pathological tooth attrition between the patients having different malocclusions and asking for orthodontic treatment. There was an analysis of 1010 clinical cases of patients from 8 to 55 years old, who’ve been receiving treatment at the orthodontic department of Moscow State University of Medicine and Dentistry named after A.I. Evdokimov in a period of time from January 2002 to December 2013. Intra-oral images and diagnostic teeth models were analyzed during the investigation. Therefore, during the research it was discovered that 22% of all patients that were examined had pathological tooth wear. All of the cases were divided in groups according to MSUMD Classification (1990). To sum up, as a result of calculation there might be a conclusion that more frequently tooth attrition was registered in the cases of the distal occlusion (Class II) combined with a deep-bite. Mostly front teeth were suffering. Research also makes it clear that malocclusion plays an important role in the development of pathological tooth attrition.